Elegia Solona w „Chronicon regum Poloniae” Erazma Glicznera ze Żnina - Lewandowski, Ignacy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
In this commemorative article, the author presents the Latin translation of one of Solon’s elegies (27W) which was placed in Chronicon regum Poloniae (from Lech until Mieszko I), a 16th-century chronicle by Gliczner, who was a theologian and pedagogue born in Żnin. In addition, mentions of the Polish studies and contemporary translations of that elegy were made, and based on the Latin translation, a Polish translation was produced in prose poetry.